2022
DOI: 10.25008/abdiformatika.v2i1.147
|View full text |Cite
|
Sign up to set email alerts
|

Pelatihan Digital Marketing Untuk Meningkatkan Penjualan Bagi UMKM Tajur Halang Makmur

Abstract: Pada masa pandemi covid 19 yang berdampak pada semua sektor di Indonesia salah satunya adalah sektor perdagangan, seperti halnya UMKM banyak yang mengalami penurunan produktivitas dan pendapatan. Pelaku UMKM harus menghadapi tantangan bisnis dengan beradaptasi dan berinovasi untuk mempertahankan dengan bertransformasi ke ranah digital. Pelaku usaha harus memiliki ketrampilan dalam memanfaatkan teknologi untuk membantu memperluas pasar dan meningkatkan penjualan. Kami mengusulkan kegiatan pelatihan bagi pelaku … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
0
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 4 publications
0
0
0
2
Order By: Relevance
“…Meanwhile, training on product marketing is expected to improve the ability of Micro, Small and Medium Enterprises (MSMEs) products in Dukun Gresik to compete with other products and build a strong brand identity to attract customers to research conducted by Ariyani et al (2022) and Kurniawan et al (2020) who revealed that packaging design can influence the branding of MSMEs and increase the selling power of their products. Digital marketing can also increase sales of MSME products because it can reach more parties (Fahdia, 2022).…”
Section: Results and Discussion The Role Of Sharia Cooperatives As Id...mentioning
confidence: 99%
“…Meanwhile, training on product marketing is expected to improve the ability of Micro, Small and Medium Enterprises (MSMEs) products in Dukun Gresik to compete with other products and build a strong brand identity to attract customers to research conducted by Ariyani et al (2022) and Kurniawan et al (2020) who revealed that packaging design can influence the branding of MSMEs and increase the selling power of their products. Digital marketing can also increase sales of MSME products because it can reach more parties (Fahdia, 2022).…”
Section: Results and Discussion The Role Of Sharia Cooperatives As Id...mentioning
confidence: 99%
“…Program ini juga mencerminkan komitmen untuk mendukung pengembangan potensi lokal dan menciptakan lingkungan yang mendukung pertumbuhan bisnis kecil dan menengah dalam menghadapi tantangan era digital. (Fahdia et al, 2022) Program digital marketing adalah serangkaian strategi, taktik, dan aktivitas yang dirancang untuk mempromosikan produk, layanan, atau merek melalui media digital dan online. Tujuannya adalah untuk mencapai target audiens secara efektif dan mempengaruhi mereka untuk melakukan tindakan tertentu, seperti membeli produk, mengisi formulir, berlangganan newsletter, atau melakukan interaksi lain yang diinginkan oleh pemasar (Arifuddin & Alimuddin, 2023) Dalam pendahuluan ini, kami akan membahas latar belakang program, tujuan, dan relevansinya dalam memanfaatkan digital marketing.…”
Section: A Pendahuluanunclassified
“…The development of the internet in the era of digitalization has also opened up digital business opportunities for entrepreneurs, such as the business providing entrusted services (jastip) which is developing in Indonesia (Syauqina & Ichsan, 2022). In addition, digital marketing training has been proven effective in increasing sales for MSMEs (Fahdia et al, 2022). Adoption of a digital marketing model can also help micro businesses to support the marketing of the products they produce (Handajani et al, 2019).…”
Section: Digitalizationmentioning
confidence: 99%